Two Inuit boys on board whaling schooner Era, Cape Fullerton, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1905)
Two Inuit boys identified as Charles and Mulse[?] pose inside the deckhouse of the whaling schooner Era at Cape Fullerton, Hudson Bay, 1905 . Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as # 4 and # 59. Original caption identifies images as ""Charles & Mulse [?] Native boys."" The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.